2020
DOI: 10.1021/acs.jpclett.0c00157
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Specific Two-Dimensional Electronic Sum Frequency Generation Spectroscopy

Abstract: High even-order surface/interface specific spectroscopy has the potential to provide more structural and dynamical information about surfaces and interfaces. In this work, we developed a novel fourth-order interface-specific two-dimensional electronic sum frequency generation (2D-ESFG) for structures and dynamics at surfaces and interfaces. A translating wedge-based identical pulses encoding system (TWINs) was introduced to generate phase-locked pulse pairs for coherent pump beams in 2D-ESFG. As a proof-of-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 89 publications
0
37
0
Order By: Relevance
“…Electronic sum-frequency generation (ESFG) is a measurement technique that selectively interrogates the electronic density of states and structural organization of molecular junctions and has been used to study liquid surfaces, semiconductor surfaces, and buried organic:inorganic junctions. In an ESFG measurement, two pulses of light simultaneously impinge on a sample. One of these pules is a spectrally broad white light (WL) continuum that overlaps with different electronic resonances within the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic sum-frequency generation (ESFG) is a measurement technique that selectively interrogates the electronic density of states and structural organization of molecular junctions and has been used to study liquid surfaces, semiconductor surfaces, and buried organic:inorganic junctions. In an ESFG measurement, two pulses of light simultaneously impinge on a sample. One of these pules is a spectrally broad white light (WL) continuum that overlaps with different electronic resonances within the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few techniques are available for investigating liquid surfaces, not to mention the surfaces of liquid droplets. Second harmonic generation (SHG) and sum frequency generation (SFG) are two of the proven surface-sensitive methods to investigate liquid surfaces. , As a spectroscopic technique, SFG is anticipated to provide vibrational structures, , , as well as electronic characters, , both of which are essential to understanding chemical and physical properties of surfaces. Several groups demonstrated the applications of the SHG and SFG techniques in atmospheric science. , These pioneering works have shown cases of the powerful surface-specific techniques.…”
mentioning
confidence: 99%
“…Several groups demonstrated the applications of the SHG and SFG techniques in atmospheric science. , These pioneering works have shown cases of the powerful surface-specific techniques. More than two decades ago, second harmonic scattering (SHS) was developed to extend the applications of the second-order nonlinear optical techniques from planar surfaces to curved surfaces. Later, vibrationally sum frequency scattering (VSFS) was further developed to characterize vibrational chemical structures of micrometer to a few nanometer particle surfaces suspended in liquids. ,, On the other hand, the development of electronic SFG and SHG spectroscopies has been left behind, even with tremendous effort. , For example, Shen et al showed interfacial electronic structure of molecules by tuning laser wavelengths . Eisenthal et al measured surface polarity at the air/water interface and interfacial electronic transition of a dye on TiO 2 surfaces .…”
mentioning
confidence: 99%
“…[185] Deng et al used 2D electronic sum-frequency generation (ESFG) to study the couplings of surface states for GaAs (111) and observed the surface dark state, which may not be revealed from conventional (1D) ESFG spectra. [186] Bian et al demonstrated that molecular structure and surface dynamics may be revealed by 2D-IR spectroscopy. [96] The effect of the interaction between metallic NPs and the surrounding materials on the ultrafast plasmon dynamics of Au NPs has also been discussed by Chen et al [187] However, applications of these studies to metallic NPs, especially those in colloids, are still rare.…”
Section: Some Other Spectroscopic Methodsmentioning
confidence: 99%
“…used 2D electronic sum‐frequency generation (ESFG) to study the couplings of surface states for GaAs (111) and observed the surface dark state, which may not be revealed from conventional (1D) ESFG spectra. [ 186 ] Bian et al. demonstrated that molecular structure and surface dynamics may be revealed by 2D‐IR spectroscopy.…”
Section: Some Other Spectroscopic Methodsmentioning
confidence: 99%